TRYPTOPHAN AND INDOLEAMINE-2,3-DIOXYGENASE (IDO) IN PATHOGENESIS OF IMMUNOSUPPRESSIVE CLINICAL CONDITIONS - V. A. Kozlov; D. V. Demina (Медицинская иммунология, 2017)
Increasing amounts of literature data suggest the leading role of indoleamine 2,3-deoxygenase (IDO) enzyme in regulation of immunosuppressive mechanisms. IDO is produced, mostly, by dendritic cells, being induced, e.g., under IFNγ involvement. Its function is to provide catabolism of tryptophan, an essential amino acid. Any reduction of tryptophan levels in extracellular environment was shown to cause functional suppression of certain immune cells, and induction of T regulatory cells. Accumulation of different tryptophan catabolites may exacerbate the immunosuppressive status induced by increased IDO expression. It is assumed that the interactions between IDO, tryptophan and its catabolites largely determine a development of hypersuppressor state in tumor growth and a hypo- (or lack of) suppressor status in autoimmune and allergic diseases. This implies some novel tasks for the therapy, including a treatment aimed for reduction of the IDO activity since the latter is involved in suppressor cell induction during tumor growth. Respectively, stimulation of IDO activity may augment suppressor activity of the regulatory cells.